(untitled) (Conferencea, 2023)
The article discusses issues related to the criteria for determining antony language and the formation of syntactic antonyms in sentences and their classification. It gives linguistic criteria that form the antonyms in the Uzbek language, also defines the essence of lexical and syntactic antonyms; types of syntactic antonyms are analyzed and methods for classifying the syntacticantonyms of the Uzbek language are proposed.